(untitled) (Scientific journal of the Fergana State University, 2025)
The article describes in detail the classification of the main irrigated soils distributed in the Bukhara oasis, including old irrigated swamp-meadow, barren meadow, barren, barren, barren-meadow, sandy-desert, gray-brown, gray-brown meadow soil types.